1969
DOI: 10.1136/jcp.22.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of plasma cobalamins in control subjects and in cases of vitamin B12deficiency

Abstract: SYNOPSIS A method for thin-layer chromatography and bioautography of plasma cobalamins is described. It requires only 5 ml of blood.Results are reported in 35 healthy people and hospital controls, and in 14 cases of untreated pernicious anaemia. In the control group there were two major components, methylcobalamin and a component which is probably a mixture of hydroxocobalamin and deoxyadenosyl cobalamin. Many cases of untreated pernicious anaemia showed a characteristic pattern in which methylcobalamin was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…In a vegan who did not receive any B,,. supplement Linnell et al (1969) found a serum %. value of 100 pg/ml, measured by the isotopic assay that we also used.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a vegan who did not receive any B,,. supplement Linnell et al (1969) found a serum %. value of 100 pg/ml, measured by the isotopic assay that we also used.…”
Section: Introductionmentioning
confidence: 96%
“…The concentration of true cyanocobalamin in the blood may be raised in tobacco amblyopia and hereditary optic neuropathies in the presence of a normal total B1, level; this rise is thought to be functionally unimportant (Wilson et al, 1971;Matthews 1971). The other important feature shown by bioautography is that methylcobalamin is biologically the most important fraction of vitamin B1, and that this is the fraction which is depleted in pernicious anaemia and not hydroxocobalamin, which may in some cases be the predominant component (Linnell et al, 1969). In view of this, the earlier suggestion of Smith (1961a, 1961b) that the difference between values A and B represents the amount of hydroxocobalamin in the blood and that this is the physiologically active fraction concerned with the detoxication of cyanide appears untenable.…”
Section: Introductionmentioning
confidence: 99%
“…The standard protocols for extraction and purification of Cbls from biological samples involve heated ethanol extraction, treatment with very alkaline or acidic solutions, and a final organic-phase extraction step (13)(14)(15)(16)(17). The major Cbls extracted and identified in these early studies included methylcobalamin (MeCbl), adenosylcobalamin (Ado-Cbl) and aqua(hydroxo)cobalamin (H 2 OCbl + /HOCbl) [reviewed by Gimsing and Nexo (18)].…”
Section: Introductionmentioning
confidence: 99%
“…In the method we have developed the plasma extracts are run on thin-layer chromatograms with precautions againstlight, and the separated cobalamins, which are quite invisible, are identified by the growth-response of a B1,-dependent organism (Linnell et al, 1969c). The resulting spots, stained crimson with a redox indicator, can thus be located, and estimated by photometric scnng.…”
Section: Techniquementioning
confidence: 99%